A multi‐component evaluation framework of a state‐wide preventive health program: My health for life. (15th March 2022) - Parkinson, Joy; McDonald, Nicole; Seib, Charrlotte; Moriarty, Stephanie; Anderson, Debra
Abstract: Issue: Chronic disease is a growing problem affecting approximately half of all Australian adults. In response to growing calls for action on chronic disease, the My health for life program was created, aimed at improving the health of individuals at high risk of developing preventable chronic disease. The preventive health program is multi‐modal, cross‐culturally tailored and contains complex social marketing, community engagement, risk assessment and health promotion components. Therefore, a multi‐component evaluation framework is essential to understand the effectiveness of the My health for life program. This brief report details the evaluation. Methods: The evaluation design uses non‐randomised, longitudinal analysis using repeated measures, observational, program goal‐based and pretest‐posttest design features to assess the program, its specific modalities and its program adaptations. To ensure timely and credible evaluation, different evaluative implementation frameworks and methods are considered. Quantitative and qualitative methods collect an array of program data at differing levels to assess the processes, outcomes and impacts of My health for life . Discussion: The implemented evaluation framework has allowed measurement of: (i) process impacts including uptake, retention and attrition, participant satisfaction, fidelity and program stakeholder engagement and (ii) outcomes relating to individual participant level changes in health behaviours. So what?: This evaluation is an example of an integrated evaluation approach in a large successful preventive health program. Findings from the evaluation will ultimately inform the applicability and transferability of the program and inform policy makers, stakeholders and other health professionals in preventive health practice.